PENGKAJIAN LANDASAN TEORI MANAJEMEN LINGKUNGAN DAN BUDAYA SERTA IMPLEMENTASINYA DALAM ORGANISASI MODERN - Shelty D. M. Sumual; Joulanda A. M. Rawis; Gracia A. G. Rorong; Felly A. Toad; Rillya Manoppo (STKIP Pesisir Selatan, 2025)
Environmental management and cultural management represent two strategic pillars in the development of modern organizations, particularly within the context of global changes characterized by climate crises, digital transformation, and shifting social values. This article provides a narrative review of the theoretical foundations of both fields by examining more than 60 relevant publications. The analysis indicates that systems ecology, sustainability theory, environmental adaptation, and stakeholder theory serve as strong foundations for implementing environmental management focused on ecological balance and resource efficiency. Meanwhile, organizational culture theory, Hofstede’s cultural dimensions, cross-cultural management, and cultural adaptation offer a comprehensive understanding of internal social dynamics influencing organizational behavior. The integration of both theoretical domains has been shown to enhance operational effectiveness, strengthen cultural identity, reduce environmental risks, and expand organizational social legitimacy. This article emphasizes that integrating environmental and cultural management is a key strategy for building organizations that are competitive, sustainable, adaptive, and culturally relevant. Future research is recommended to develop integrative empirical models and conduct cross-sector comparative studies